What the Spectrum of Microglial Functions Can Teach us About Fetal Alcohol Spectrum Disorder - Wong, Elissa L.; Stowell, Rianne D.; Majewska, Ania K. (Frontiers in Synaptic Neuroscience, 2017)
Alcohol exposure during gestation can lead to severe defects in brain development and lifelong physical, behavioral and learning deficits that are classified under the umbrella term Fetal Alcohol Spectrum Disorder (FASD). Sadly, FASD is diagnosed at an alarmingly high rate, affecting 2-5% of live births in the United States, making it the most common non-heritable cause of mental disability. Currently no standard therapies exist that are effective at battling FASD symptoms, highlighting a pressing need to better understand the underlying mechanisms by which alcohol affects the developing brain. While it is clear that sensory and cognitive deficits are driven by inappropriate development and remodeling of the neural circuits that mediate these processes, alcohol’s actions acutely and long-term on the brain milieu are diverse and complex. Microglia, the brain’s immune cells, have been thought to be a target for alcohol during development because of their exquisite ability to rapidly detect and respond to perturbations affecting the brain. Additionally, our view of these immune cells is rapidly changing, and recent studies have revealed a myriad of microglial physiological functions critical for normal brain development and long-term function. A clear and complete understanding of how microglial roles on this end of the spectrum may be altered in FASD is currently lacking. Such information could provide important insights toward novel therapeutic targets for FASD treatment. Here we review the literature that links microglia to neural circuit remodeling and provide a discussion of the current understanding of how developmental alcohol exposure affects microglial behavior in the context of developing brain circuits.